Decomposing of Urban Poor / Non-Poor Differential in Childhood Malnutrition and Mortality in India, 2015-16 - Ujjwal Das (International Journal of Engineering and Management Research, 2020)
Background The high level of childhood malnutrition due to mortality in India is a major hurdle impeding the achievement of the Sustainable Development Goals–3 (SDG–3). The present study aims to quantify the contribution of factors that explain the poor/non-poor gap in malnutrition and mortality status of children 0-5 years in urban India using data from 2015-16 of fourth round National Family Health Survey (NFHS-4). Methods For understand the gap in child health between the urban poor and non-poor, and across the selected covariate were used the descriptive statistics. Furthermore Blinder–Oaxaca decomposition and non-liner Fairlie decomposition technique both were used to explain the factors contributing to the average gap in under nutrition between poor and non-poor children in urban India. Result The result suggested that explained the gap urban poor/non-poor in nutritional indicator stunting and underweight were 40 and 46 percentage and childhood infant and under-five mortality were 40 and 48 percentage respectively. The maternal factor mainly for lower education contributed much more changed in child health status those are living in urban poverty. Conclusion The overall finding indicate that children living poor household higher level malnutrition and mortality due to poor health status and poor education of mother, lower health care service and less exposed to mass media. This finding help to policy maker reducing the gap of child undernutrition between urban poor and the non-poor and low coverage of health services among the urban poor.